The Rowling Protocol, Steven Bannon, and Rogue POTUS Staff: a Study in Computational Authorship Attribution - Juola, Patrick (Language and Law / Linguagem e Direito, 2019)
A key step forward in the professionalization of forensic science is the development of standards of practice and protocols. Based on his analysis of the Rowling case, Juola (2015) proposed a systematic protocol for authorship verifi- cation. We present both a theoretical and an empirical analysis of the accuracy of this protocol. We further present a demonstration of this analysis in terms of a high-profile case of political activism. We show that this protocol produces accurate and understandable analyses of the likelihood of common authorship.